KOMPETENSI PENULISAN KARYA ILMIAH GURU DALAM PERSPEKTIF AGIL - Mulyana, Mulyana; Wicaksono, Luhur; Junanto, Tulus; Millah, Roihatul (Universitas Muhammadiyah Surakarta, 2023)
This study analyzes academic writing competence among teachers at SMA Negeri 6 Pontianak using Talcott Parsons' AGIL theory. This study involves nine teachers with job classifications IVa/b as participants. Employing qualitative methods, data were collected through in-depth interviews, academic paper observations, and performance document reviews. In the digital age, writing skills are crucial for educators adapting to evolving education trends. Findings reveal inadequate adaptation to educational policies and limited commitment to teacher professionalism. Despite achieving commitment to academic writing, teachers focus on cognitive goals, neglecting practical applications in the classroom and facing resource planning constraints. There is a moderate integration of research findings into teaching tasks. Competence development is sporadic, with a significant percentage having not undergone training, and All respondents lack support for research funding latency. Urgent actions are necessary to improve teachers' policy adaptation, broaden academic writing goals to include practical applications, enhance resource planning, and provide consistent support for competence development through training and financial assistance. This research emphasizes the critical need for comprehensive improvements to address current challenges in teacher professionalism and academic writing competencies, contributing valuable insights for educational policy and practice